The development and evaluation of a preschool language enrichment programme: can a practitioner-delivered, multi-tiered, short-term intervention improve early language outcomes? - Gardner, R (2023)
Early language skills are crucial for the later development of reading. This research aimed to develop and evaluate an Early Years enrichment programme, designed to improve the oral language skills of at-risk pre-schoolers, prior to school entry. The 10-week programme was developed based on the literature. It focussed on ten children’s picture books, around which all the activities were centred. The highly-structured programme consisted of both a daily universal element, delivered to the whole class, and small group and 1:1 sessions, which were targeted at the six children in each class with the poorest language abilities. A novel early language measurement tool, the LanguageScreen app, was assessed for its suitability for use alongside the NELIP programme, as both a primary outcome measure and a means to identify children with poor language skills. A cross-sectional sample of 309 children (aged 3-6 years) were recruited from three nursery classes. Analyses of these data showed that the LanguageScreen app had acceptable reliability and criterion validity. A factor analysis demonstrated that scores on the four subtests contributed to a single factor, and so could be combined to produce a factor score: representative of general oral language ability. To assess the efficacy of the NELIP programme an RCT was conducted. Six nursery classes were recruited (children, n=137). Half were allocated to deliver the intervention, and half to a business-as-usual control group. LanguageScreen data and intervention vocabulary scores were collected for all participating children. ANCOVA analyses demonstrated that the children who received the intervention did not achieve significantly higher scores than those in the control group, at either immediate or delayed post-test. A qualitative investigation was performed on data collected from a practitioner feedback survey. The lack of a measurable impact of the programme on language skills was in contrast to what was expected from the literature. Potential reasons for this null result are explored in the discussion.